Depression in Athletes. Issue 1 (January 2015) - Wolanin, Andrew; Gross, Michael; Hong, Eugene
<x xml:space="preserve">Abstract</x> Depression affects an estimated 6.7% of today's adult population in a 12-month period. The prevalence rates for certain age groups, such as young adults and older adults, are higher. There are approximately 400, 000 National Collegiate Athletic Association student athletes competing each year and 5 to 7 million high school student athletes involved in competitive interscholastic sports. Given such a high prevalence rate in certain age groups and a large denominator pool of athletes, past notions that athletes are devoid of mental health issues have come under scrutiny by sports medicine providers. Initial data suggest that athletes are far from immune to depression. The purpose of this article was to review the current research on athletes and depression; particularly this article will provide an overview of studies, which have investigated the rate of depression among athletes, and discuss relevant risk factors, which may contribute to depression among athletes.